Effect of relining on fiber post retention to root canal - André Luís Faria-; Celso de Freitas Pedrosa-Filho; Murilo de Sousa Menezes; Daniele Machado da Silveira; Luís Roberto Marcondes Martins (University of São Paulo, 2009)
One of the clinically relevant problems dentists face when restoring endodontically treated teeth is the mismatch between fiber post and post space diameters, which results in an excessively thick resin cement layer. Fiber post relining appears as a solution for this problem. OBJECTIVES: The aim of this study was to evaluate the effect of fiber post relining with composite resin on push-out bond strength. MATERIAL AND METHODS: Twenty bovine incisors were selected to assess post retention. The crowns were removed below the cementoenamel junction and the root canals were treated endodontically and flared with diamond burs. The roots were allocated into two groups (n=10): G1: fiber posts without relining and G2: fiber posts relined with composite resin. The posts were cemented with a dual-cured resin cement and the specimens were sectioned transversally. Three 1.5-mm thick slabs were obtained per root and identified as cervical, medium and apical thirds. The push-out test was performed at a crosshead speed of 0.5 mm/min until post dislodgement occurred. The failure mode of fractured specimens was analyzed under scanning electron microscopy. Data were analyzed by split-plot ANOVA and post-hoc Tukey's test at a pre-set alpha of 0.05. RESULTS: Relined fiber posts presented higher retention values than non-relined post in all thirds. No statistically significant differences (p>0.05) were found among thirds for relined posts. All failures occurred at the interface between resin cement and root dentin. CONCLUSIONS: Relining with composite resin seems to be an effective method to improve the retention of fiber posts to flared root canals.